Ob arhaičeskih čertah narodnoj kul’tury rusin Vostočnoj Slovakii On the Archaic Features of the Ruthenian Folk Culture in Eastern Slovakia - M. Valentsova, Marina (Studia mythologica Slavica, 2019)
<span style="line-height: 115%; font-family: ’Helvetica’,’sans-serif’; font-size: 11pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-font-family: AGaramondPro-Italic; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">This article continues the study of Ruthenian spiritual culture and aims at the determination of ancient elements in the selected rituals and their parts in folk meteorology, wedding, funeral and birth ceremonials, and beliefs about animals and birds in the all-Slavic context. It is shown that the traditional Ruthenian culture is very close to the West Ukrainian ones on the one hand and that it has substantive differences, which allow considering Ruthenian tradition a separate East-Slavic tradition with deep historical background.